2015
DOI: 10.1007/s00436-015-4594-9
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic relationships of endemic Australasian trichostrongylin families (Nematoda: Strongylida) parasitic in marsupials and monotremes

Abstract: The phylogenetic relationships of the endemic (or largely endemic) Australasian trichostrongylin nematode families Herpetostrongylidae, Mackerrastrongylidae and Nicollinidae as well as endemic trichostrongylin nematodes currently placed in the families Trichostrongylidae and Molineidae were examined using the complete large subunit (28S) ribosomal RNA gene. The Herpetostrongylinae proved to be monophyletic. However, representatives of the Nicollinidae nested with the Herpetostrongylinae. The Mackerrastrongylid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Moreover, the results of our molecular phylogenies indicated that the genus Boehmiella belongs to a family distinct from the Australasian trichostrongylins of the families Herpetostrongylidae that are known from Australian marsupials and reptiles in Australia and south-east Asia, and Nicollinidae which occurs in monotremes. Chilton et al (2015) demonstrated for the first time the close phylogenetic relatedness between Herpetostrongylinae and Nicollinidae, a result also found in our analyses. However, Boehmiella does have a number of morphological traits that are found in herpetostrongylids and nicollinids, such as the robust esophageal neodont, and the complex spicules and reduced dorsal lobe in the caudal bursa, which we interpret as simplesiomorphic characters shared by the Boehmiellidae fam.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the results of our molecular phylogenies indicated that the genus Boehmiella belongs to a family distinct from the Australasian trichostrongylins of the families Herpetostrongylidae that are known from Australian marsupials and reptiles in Australia and south-east Asia, and Nicollinidae which occurs in monotremes. Chilton et al (2015) demonstrated for the first time the close phylogenetic relatedness between Herpetostrongylinae and Nicollinidae, a result also found in our analyses. However, Boehmiella does have a number of morphological traits that are found in herpetostrongylids and nicollinids, such as the robust esophageal neodont, and the complex spicules and reduced dorsal lobe in the caudal bursa, which we interpret as simplesiomorphic characters shared by the Boehmiellidae fam.…”
Section: Discussionsupporting
confidence: 89%
“…The earliest bovids appeared 20 mya, 3 and since T. circumcincta is seen in sheep and goats but not cattle, we can safely assume their divergence from related nematode species occurred following or alongside bovid divergence. Chilton et al 47 49 have shown the evolutionary relationships between T. circumcincta (sheep and goats), O. ostertagi (cattle), and H. contortus (sheep and goats), and that they are very closely related. There was no similar protein detected in this study between T. circumcincta and O. ostertagi , the more closely related of these 3 species, but there was a protein detected from H. contortus ( Table 1 ), a slightly more distant species but still within the same Trichostrongylidae clade and with the same host species.…”
Section: Discussionmentioning
confidence: 99%
“…Coevolutionary relationships between the herpetostrongyline nematodes and their marsupial hosts have been suggested based on morphological (summarised in Beveridge and Spratt 1996, fig. 8) and molecular (Chilton et al 2015) data. Basal taxa occur in dasyurid marsupials, with subsequent diversification to the peramelids and then to the diprotodontids (possums, rat-kangaroos, wallabies and kangaroos).…”
Section: Marsupials and Monotremesmentioning
confidence: 99%
“…Evidence for some connection between the South American and Australian marsupial fauna is provided by the cestode genus Paralinstowia, which occurs in didelphid marsupials in South America and peramelid marsupials in Australia (Beveridge and Spratt 1996). Both morphological and molecular evidence suggest that the endemic nematode family Mackerrastrongylidae may have its origins in echidnas, which presumably existed on the continent before the arrival of the marsupials, but subsequently invaded dasyurid and peramelid marsupials (Chilton et al 2015). The original Australian marsupials were carnivores and therefore the presence of parasite groups primarily parasitic in herbivores can most readily be explained by the subsequent arrival of herbivores (rodents) from Asia.…”
Section: Marsupials and Monotremesmentioning
confidence: 99%
See 1 more Smart Citation